The growing influence of China in the Middle East and its implications for US relations - Abdul Samad, Khaldoun (Arab Journal for Sciences and Research Publishing, 2024)
The Arab region has become a focal point of geoeconomic competition between China and the United States. As China’s global influence has grown, the U.S. has shifted from strategic partnership to strategic competition, reflecting broader shifts in the international system. This dynamic is playing out in the Arab region, which has become a key battleground. China is pursuing economic initiatives like the Belt and Road to expand its presence, while the U.S. is countering with its own projects. The research examines this complex landscape, exploring the economic realities, strategic importance, and direct/indirect competition between the two powers in the region. The analysis finds that the Belt and Road Initiative is a crucial element in strengthening China-Arab economic ties, with China providing substantial funding for infrastructure projects to attract regional partners. However, this also raises challenges around economic dependence and American concerns. Ultimately, the Arab region must navigate these competing influences, leveraging economic diversification and global relationships to pursue stability and sustainable growth. Both Western and Eastern powers will continue to vie for influence, underscoring the region’s strategic importance and the need for a balanced, pragmatic approach.